Women Economic Empowerment and Poverty Reduction: A Case Study of Kabale Municipality. - Gerald, Baguma (Kabale University, 2022)
A Dissertation Report Submitted to the Directorate of Postgraduate Training in Partial Fulfilment of the Requirement for the Award of Master of Arts Degree in Project Planning and Management of Kabale University